Nyttjande av korsningar i mjölkproduktionen - Andersson, Magdalena (2009)
Farmers’ main reason for crossbreeding dairy cows is that they have seen a decline in functional traits, especially in the Holstein breed. Throughout crossbreeding, the farmers can combine functional and production traits of different dairy breeds and utilize the heterosis effects which emerge when two or more breeds are crossed. Results from different studies with Holstein crossed with Jersey, Brown Swiss, Normande and Scandinavian Red have shown that the crosses had higher fertility, longer productive life, had fewer stillborn calves and had easier calvings than purebred Holstein. The Holstein crosses have shown very good results and sometimes even better than the purebred Holstein for fat production, which gave higher amount of energy corrected milk (ECM) and higher income for the farmers. Heterosis effects in the crossbreeds had favourable results in both conventional and pasture-based systems. There was no difference between different rotational crossing systems practised. Instead the crossbreds were economically sustainable for the farmers since they had longer productive life, higher fertility and they were healthier than the purebred Holstein. It was also economically sustainable for farmers to use crossbreds due to their effects of heterosis in both functional and production traits. However, both breeders and farmers need to consider that the heterosis effects in the crossbreeds may be differently expressed in different environments and that the genetic gain needs to be continued in the purebred populations.